Zasebnost v informacijski družbi - Kovačič, Matej (Teorija in praksa, 2000)
The article addresses the problem of privacy in modern information society. The need for organisation and collecting of information is constantly increasing and consequently threats the privacy. Threat to privacy is raising by modern information and communication technologies on one side, while one the other side one use modern technology - criptography - as a tool for prevention of privacy. However, because cryptography could be abused for hiding criminal activities, a group of opponents of cryptography's use, especialy on the side of the state and its repressive organs, was formed. There are also activists for human rights and freedoms, who believe the cryptography to be one of the basic democratic tools of information society. But it seems that gains of unlimited cryptography use outweight the possible negative effects. Or as procryptography activists put it: if freedom of speech is one of the basic principles of democratic society, then the use of cryptography is its natural consequence.
Keywords: Privacy; Zasebnost; Informacijska družba; Information society; Zaščita podatkov; Data protection; Zaščita pravic; Protection of rights; information technology; informacijska tehnologija; varstvo podatkov; kriptografija